O pescador e o professor: as jornadas da experiência : uma abordagem sobre educação desde e para a experiência junto a estudantes de arte - Orloski, Erick [UNESP] (2015)
This doctoral thesis is about the education from and for experience, based on Imanol Aguirre's concept, in dialogue with the concepts of experience and aesthetic experience based in Jorge Larrosa and John Dewey, and in dialogue too with the educational thought of Paulo Freire. For this, were collected stories of college's students of arts and pedagogy, which made subjects taught by the researcher and, based on this stories, thematic approaches were made around the central research theme, in a building of an education from and for experience concept. The thesis is divided into two parallel narratives, which develop during the three acts: one is the Fisherman's narrative, fictional and metaphoric, and the other is the Teacher's narrative, based on the concepts and the stories, not only students' stories, but the researcher's stories, in dialogue with the author's ideas